Sexual Violence Discourse on Internet: Meme, Hoe and the Case of Eno Fariha - Randie Ananda Agam (Yayasan Jurnal Perempuan, 2016)
Internet memes are presently gaining momentum as the hip media of the internet, yet it also brought the dated notion of sexism and violence against women. The notion is apparent especially after the recent case of violence and murder of Eno Fariha was transformedinto memes. Using several superficial aspect of media coverage on Eno’s case, such as the utilization of hoe for the murder, the creator of said memes basically implies that any women who violate practices identifiable with certain religion is subject to similar act of violence which befalls Eno. Moreover, taking into account that internet memes are made ‘just for laughs’, the humor of the meme becomes more prevalent than the violence discourse. Further inspection is needed on how much has the discourse spread, especially with memes’ quick and easy spread through the internet, and on its discursive relation with religion and domestification of women.